Assertive Form of the Local Citizen to Refugees in Pekanbaru Indonesia - Happy Wulandari; Abdul Mu'ati Ahmad; Jusang Bin Bolong (UIN Salatiga, 2021)
In other situations, dissimilarity such as in language difficulties between host community and refugees would lead to a problem. Regardless, both local citizens and refugees in the Pekanbaru city research area can develop good relations. Indonesia is known as a country with assertive behavior, therefore by using qualitative, this research looks at the manifestation of that assertiveness. The discovery may contribute to the discussion of the Indonesia-refugees theme in the global academic level and intercultural communication act in Indonesia. The study found that the locals prefer appropriate behavior over language ability as the engagement factor for their sustainability relationship with refugees. When they are in conversation and face difficulty in language, the locals will enthusiastically wait for the refugees to finish their sentences, listen to the words spoken by refugees, and try out their meaning.